1995
DOI: 10.1111/j.1460-9568.1995.tb00686.x
|View full text |Cite
|
Sign up to set email alerts
|

Laufband Therapy Based on‘Rules of Spinal Locomotion’is Effective in Spinal Cord Injured Persons

Abstract: Rehabilitation of locomotion in spinal cord (s.c.) injured patients is unsatisfactory. Here we report the effects of a novel 'Laufband (LB; treadmill) therapy' based on 'rules of spinal locomotion' derived from lower vertebrates. Eighty-nine incompletely paralysed (44 chronic and 45 acute) para- and tetraplegics underwent this therapy, then were compared with 64 patients (24 chronic and 40 acute) treated conventionally. The programme consisted of daily upright walking on a motor driven LB initially with body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
275
4
4

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 460 publications
(291 citation statements)
references
References 10 publications
8
275
4
4
Order By: Relevance
“…Functional walking was assessed in two ways: (1) by measuring the walking speed, distance walked and %BWS provided during a typical treadmill session and (2) using a modified version of a scale developed by Wernig et al 3,7 to evaluate over ground walking abilities (see Table 2). …”
Section: Assessment Of Functional Walkingmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional walking was assessed in two ways: (1) by measuring the walking speed, distance walked and %BWS provided during a typical treadmill session and (2) using a modified version of a scale developed by Wernig et al 3,7 to evaluate over ground walking abilities (see Table 2). …”
Section: Assessment Of Functional Walkingmentioning
confidence: 99%
“…Studies in both the acute [1][2][3][4] and chronic 3,[5][6][7] SCI population have shown that functional walking ability can be improved with BWSTT in patients with motor-incomplete (American Spinal Injury Association Classification (ASIA) C or D) paraplegia or tetraplegia. These results are certainly encouraging, but a number of issues need to be resolved before BWSTT becomes accepted as a standard form of rehabilitation after SCI.…”
Section: Introductionmentioning
confidence: 99%
“…In man after complete spinal transection, only elements of stepping but no full step cycles may be evoked on the treadmill. 5,6,12 Improvement of stepping in spinal cord injured cats and monkeys was achieved by intensive treadmill-stepping; 1,2 other training regimes such as daily standing were not successful and even signi®cantly worsened stepping capabilities in cats. 15,18 Translated into strategies for motor rehabilitation of spinal cord injured patients, these observations imply that relearning of walking can be done only by intensive exercise of upright walking.…”
Section: Introductionmentioning
confidence: 99%
“…Treadmill training has been used with considerable success in people with SCI, classified as functionally incomplete, 352 that is, with retention of some sensory or motor function below the level of injury (ASIA scale B-D). Persons were selected if they had some voluntary activity in leg muscles, had mobile joints, had no spasticity and if they lacked complications such as ulceration or infection.…”
Section: Practice Makes Perfectmentioning
confidence: 99%
“…Follow-up studies in persons with incomplete injuries were encouraging and showed that improvements made during a few weeks to months of treadmill training were maintained for 6 months to 6 1/2 years after training ceased. 352,353 The long-term effects of treadmill training have recently been compared for individuals that are functionally incomplete and complete. 354 After training (15 min daily, 5 days per week for several months), persons with incomplete injuries showed significant improvements and could use their new locomotor capabilities for overground walking for at least short distances.…”
Section: Practice Makes Perfectmentioning
confidence: 99%